Health-Related Quality of Life, Financial and Psychosocial Impact on Parents Having Children with Nephrotic Syndrome (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Childhood nephrotic syndrome (NS) follows a chronic course in most children. However, little has been studied about the burden of NS on the caregivers despite evidence that caregiver burden or impairment in their well-being may alter the outcome of chronic childhood illnesses. We aimed to study the multi-dimensional impact on the quality of life (QOL) of families of children with the NS to determine the significant predictors of caregiver burden and psychological distress among caregivers of children with NS in terms of Parents HRQOL (health related quality of life), Pediatrics Health-related quality of life Family Impact Module (PedsQLTM FIM) and Family Functioning Summary Score (FaF-SS).Methods: This cross-sectional analytical study was conducted over a period 6 months from October 2019 to March 2020. Parents of children with diagnosed nephrotic syndrome (frequent relapsers, steroid dependent and steroid resistant), on treatment for at least one year, attending at the Outpatient and In-patient Units of Pediatric Neprology, Dhaka Medical College & Hospital (DMCH) and Dhaka Shishu Hospital were taken as cases. A total of 40 cases and 64 controls were consecutively included in the study. The control group consisted of parents of healthy age-sex matched children attending at the immunization clinic to have their children immunized. Data were collected by face-to-face interview of the parents using questionnaire of Pediatric Quality of Life Inventory 4 (PedsQLTM), Family Impact Module (FIM). PedsQL FIM is a multi-item scale comprising of 36 questions grouped under eight domains related to physical functioning, emotional functioning, social functioning, cognitive functioning, communication, worry, daily activities and family relationships.Results: Parents HRQOL-SS was compromised with certain aspect of their demographic characteristics. Parents with debt and widows had compromised HRQOL than the parents without debt and both of the spouses are living together (p = 0.174 and p=0.027 respectively). Parents whose children responding well to treatment had a better HRQOL than those whose children were not responding to treatment (p = 0.102). As PedsQLFIM-SS was compared between the demographic characteristics of the parents, again widows and parents with debt had significantly worse PedsQLFIM-SS (p = 0.007 and p = 0.038 respectively). Parents with debt also had impact on family functioning as evidenced by commendably reduced FaF-SS (family functioning summary score) in parents with debt than those in parents without debt (p = 0.029). There was no difference between case and control groups in terms of Parents HRQOL-SS and FaF-SS (956.8 ± 195.9 vs. 970.9 ± 287.7, p = 0.786 and 404.5 ± 87.8 vs. 391.4 ± 119.1, p = 0.549 respectively) and each of the six individual domains, except emotional functioning which was significantly poor in the case group than that in the control group (p = 0.005) Physical functioning was also considerably worse in the case group than that in the control group, although the difference was not statistically significant (p = 0.130).Conclusion: The study concluded that parents of the children with NS suffer from immense financial, physical and psychological burden. Burden is significantly greater for widows or when the families are in debt due to continued effort to cope with the stresses resulting from caregiving of their compromised children. Early diagnosis and treatment of parents’ burden is of utmost need to help improve parents’ health-related quality of life.Ibrahim Card Med J 2021; 11 (1): 28-34